Sacred music - a forbidden fruit - Jonane, Julija (Muzikološki zbornik, 2014)
Prohibition of sacred music during the period of Soviet Latvia was exerted like a syndrome of forbidden fruit, that was breached in the underground way and developed in secret and complicated forms, in which the central is secular music genres' and radical musical language's using. A re-reading of texts will lead to a more nuanced understanding of the development of sacred music in Latvia and other countries.
Keywords: Latvija; latvijska glasba; razvoj duhovne glasbe; sovjetska glasba; zgodovina duhovne glasbe